Development of a Novel Cesium Adsorbent which Causes Minimal Hydraulic Resistance through the Immobilization of Prussian Blue Analogues in a Monolithic Silica-Alumina Microhoneycomb - S.R. Mukai (Chemical Engineering Transactions, 2014)
Prussian blue analogues (PBAs) such as K2[CuFe(CN)6] are expected to become the key material for efficient cesium recovery. However to use this material efficiently, it must have a morphology that doesn’t cause a severe hydraulic resistance, as a high throughput is required during recovery. This is very difficult, as this material is usually obtained in the form of small particles. In this work, we developed a cesium adsorbent with a low hydraulic resistance using PBAs as the adsorption sites. Silica-alumina was selected as the substrate. As for the morphology of the adsorbent, we adopted a microhoneycomb structure, which can be obtained by the Ice Templating Method, a new micromolding method developed in our laboratory. The obtained adsorbent showed a significantly lower hydraulic resistance than conventional adsorbents in the particle form, and could be used to continuously remove ppm-ordered cesium from solutions.